Designing of Virtual laboratory on Thermal Expansion - Darman, Dina Rahmi; Suhandi, Andi; Kaniawati, Ida; Samsudin, Achmad; Wibowo, Firmanul Catur (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to produce a virtual laboratory that can be used in teaching physics about thermal expansion. This research uses Design Development Research (DDR) with the ADDIE development model. The development results produce virtual laboratory characteristics consisting of two experiments, three independent and control variables, namely the type of material and length of the cylindrical rod, and changes in temperature, as well as the dependent variable, namely temperature. change in cylinder rod length. Data collection is carried out by asking for validator responses to the virtual laboratory that has been developed. The validators consist of five physics lecturers who are experts in learning media and physics concepts. Validation data is processed using the average percentage of expert responses. The virtual laboratory aspect of thermal expansion validation results in quality, appearance and interactivity was 96%, 93% and 92.5% with very valid criteria. The validation results for all aspects conclude that the virtual laboratory on thermal expansion is very valid with a value of 93.8% and can be used for physics learning.Keywords: virtual laboratory, thermal expansion, physics learning